Mauritius : Unemployment and the Role of Institutions - Yao, James; McDonald, Calvin (Washington, D.C. : International Monetary Fund, 2003)
Despite strong economic growth, a "U"-curve unemployment phenomenon in Mauritius can be observed. Unemployment plunged from 21 percent to less than 4 percent between the early 1980s and the early 1990s, but this trend was reversed and the rate increased to 10 percent by end-2002. This paper provides an analytical framework to explain this development. The growth of higher-skilled sectors coupled with rigidities in the labor market seem to account for the observed unemployment behavior. Policy makers can improve employment prospects by not only investing in education to reduce skills mismatch but also by reforming the pay-setting institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet